Introducing Activity-Based Payment in the Hospital Industry: Evidence from French Data - Philippe Choné; Franck Evain; Lionel Wilner; Engin Yilmaz (Center for Economic Studies and ifo Institute (CESifo), 2013)
Many countries have reformed hospital reimbursement policies to provide stronger incentives for quality and cost reduction. The purpose of this work is to understand how the effect of such reforms depends on the intensity of local competition. We build a nonprice competition model to examine the effect of a shift from global budget to patient-based payment for public hospitals in France. We predict that the number of patient admissions should increase in public hospitals by more than in private clinics and that the increase in admissions is stronger in public hospitals more exposed to competitive pressure from private clinics. Considering the reform implemented in France between 2005 and 2008, we find empirical evidence supporting these predictions.
Keywords: I11; I18; L33; 330; health care markets; prospective payment system; local competition; not-for-profit hospitals